Design and Simulation of Shift Schedule for Modular Automatic Transmission - Wang Yanzhong; Wang Dapeng; Li Yuan; Ren Shaoying; Dou Delong (Jixie chuandong)
A dynamic shift schedule is designed for the prototype of hydraulic power shift automatic transmission. The steady-state schedule cannot adapt to dynamic condition,aiming at the problems including wrong shift caused by sudden change of throttle,a four-parameter fuzzy control method is designed to modify based on throttle opening,throttle change rate,acceleration and speed. Based on the recursive least square method,a road ramp prediction and shift control schedule is designed in order to eliminate the cyclic shift. A model of vehicle is built,the result of simulation proved that the fuzzy control method successfully improve the acceleration performance and eliminate wrong shift under fast fuel filling. The ramp shifting control method can effectively identify the slope and eliminate the cyclic shift.